2011
DOI: 10.1021/ac202053y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Distribution of Intravenously Injected Adipose Tissue-Derived Stem Cells Labeled with Quantum Dots in Mice Organs through the Determination of their Metallic Components by ICPMS

Abstract: Adipose tissue-derived stem cells (ASCs) have shown promise in cell therapy because of their ability to self-renew damaged or diseased organs and easy harvest. To ensure the distribution and quantification of the ASCs injected from tail vein, several whole-body imaging techniques including fluorescence optical imaging with quantum dots (QDs) have been employed, but they may suffer from insufficient sensitivity and accuracy. Here, we report quantitative distribution of ASCs in various organs (heart, lung, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…With regard to cell transplantation into the lungs, some authors have investigated the survival rate of intravenously administerd MSCs, and found high percentages [29][30][31]. Because the duration from MSC injection to estimation of the cell counts in these studies was much shorter than the 3 and 6 weeks used in our study, our cell survival rate cannot be directly compared with the previous reports.…”
Section: Disccusionmentioning
confidence: 56%
“…With regard to cell transplantation into the lungs, some authors have investigated the survival rate of intravenously administerd MSCs, and found high percentages [29][30][31]. Because the duration from MSC injection to estimation of the cell counts in these studies was much shorter than the 3 and 6 weeks used in our study, our cell survival rate cannot be directly compared with the previous reports.…”
Section: Disccusionmentioning
confidence: 56%
“…Another FI-ICP-MS approach published by Takasaki et al [115] employed quantum dots (QD) with a Cd, Te and Se bearing core for elemental labelling of adipose tissue-derived stem cells. Due to the small sample size (approximately 1 mg) an optimized microwave assisted acid digestion procedure was developed.…”
Section: Selected Applications Of Fi- and Lc–icp-ms For Quantificatiomentioning
confidence: 99%
“…The tissue distribution of these samples is shown in Figure 5. All analyses were performed in a period of 12 Figure 7. Effect of exposure to esomeprazole strontium tetrahydrate and esomeprazole magnesium trihydrate on strontium and calcium in femur from adult and fetal rats.…”
Section: Dilution Accuracymentioning
confidence: 99%
“…Typically, an acidic or basic sample digestion is used either with the assistance of microwaves [7][8][9][10][11][12] or heating [13,14]. Although microwave digestion has a pronounced advantage in terms of speed of sample preparation, microwave treatment cannot be performed in a highly parallel manner, thereby strongly limiting sample throughput.…”
mentioning
confidence: 99%